Murispora aquatica sp. nov. and Murispora fagicola, a new record from freshwater habitat in China - Bao, Dan-Feng; Wanasinghe, Dhanushka N.; Luo, Zong-Long; Mortimer, Peter E.; Kumar, Vinit; Su, Hong-Yan; Hyde, Kevin D. (Phytotaxa, 2019)
We are currently studying lignicolous freshwater fungi in China. In this paper, we introduce two taxonomic accounts to the family Amniculicolaceae in Pleosporales viz. Murispora aquatica sp. nov (from Yunnan) and a new record of Murispora fagicola (from Tibet). The conclusions were derived from both morphological comparisons and the results of phylogenetic analyses (concatenated ITS, LSU, SSU and TEF1-α sequence data). The new species is compared with other existing species of Murispora and comprehensive descriptions and micro-photographs are provided.